2017
DOI: 10.3389/fnbeh.2017.00050
|View full text |Cite
|
Sign up to set email alerts
|

Losing without Fighting - Simple Aversive Stimulation Induces Submissiveness Typical for Social Defeat via the Action of Nitric Oxide, but Only When Preceded by an Aggression Priming Stimulus

Abstract: Losing a fight (social defeat) induces submissiveness and behavioral depression in many animals, but the mechanisms are unclear. Here we investigate how the social defeat syndrome can be established as a result of experiencing aversive stimuli and the roles of neuromodulators in the process. While biogenic amines and nitric oxide (NO) are associated with reduced aggression in mammals and insects, their specific actions during conflict are unknown. Although the social defeat syndrome normally results from compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…An alternative, or at least complementary possibility, is that the action of 5HT in losers depends on prior activation of the neurotransmitter pathway that controls the initial decision to retreat. In crickets, the decision to flee and subsequent loser depression is initiated by nitric oxide (NO) and does not require 5HT (Stevenson and Rillich, 2015 ; Rillich and Stevenson, 2017 ). Here we showed that blocking NO synthesis with LNAME either before (Figure 3B ) or after (Figure 4 ) multiple defeats prohibited long term aggressive depression even more effectively than ketanserin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative, or at least complementary possibility, is that the action of 5HT in losers depends on prior activation of the neurotransmitter pathway that controls the initial decision to retreat. In crickets, the decision to flee and subsequent loser depression is initiated by nitric oxide (NO) and does not require 5HT (Stevenson and Rillich, 2015 ; Rillich and Stevenson, 2017 ). Here we showed that blocking NO synthesis with LNAME either before (Figure 3B ) or after (Figure 4 ) multiple defeats prohibited long term aggressive depression even more effectively than ketanserin.…”
Section: Discussionmentioning
confidence: 99%
“…That used for AMTP has been shown to be the minimum required to achieve almost complete depletion of serotonin as determined by immunocytochemistry, but above that shown to achieve complete depletion as determined by HPLC (see Stevenson et al, 2000 ). The dosages for all other drugs were selected as the minimum that induced clear effects on aggression, without obvious detrimental effect on general motility as judged by eye and were established in previous investigations (Rillich and Stevenson, 2014 , 2015 , 2017 ; Stevenson and Rillich, 2015 ), or in pilot experiments for the present study (Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focuses on cricket locomotion. Cricket is one of the ideal experimental animals to investigate neuronal mechanisms underlying varieties of behaviors such as locomotion [walking (Owaki et al, 2021 ), flight (Schul and Schulze, 2001 ; Pollack and Martins, 2007 ), swimming (Matsuura et al, 2002 ), aggressive behavior (Stevenson et al, 2000 ; Sakura et al, 2012 ; Rillich and Stevenson, 2014 , 2017 ), escape behavior (Jacobs et al, 2008 ; Yono and Aonuma, 2008 ), mating behavior (Nagao et al, 1991 ; Ureshi et al, 2002 ; Nagamoto et al, 2005 ; Killian et al, 2006 ), learning and memory (Matsumoto et al, 2006 ), phonotaxis (Baden and Hedwig, 2008 ; Pollack and Kim, 2013 ), circadian rhythm (Saifullah and Tomioka, 2002 ) and so on]. On the other hand, in the robotics field, cricket inspired robots are made where design and control law of autonomous robots are investigated [the locomotion of micro-cricket robot: (Birch et al, 2000 ), phonotaxis robot: (Lund et al, 1997 ; Reeve et al, 2005 ), group behavior: (Funato et al, 2008 , 2011 ), cricket-robot interaction: (Guerra et al, 2010 ; Kawabata et al, 2013a , Kawabata et al, 2013b )].…”
Section: Introductionmentioning
confidence: 99%